Genomic Relatedness, Antibiotic Resistance and Virulence Traits of Campylobacter jejuni HS19 Isolates From Cattle in China Indicate Pathogenic Potential - Zang, Xiaoqi; Huang, Pingyu; Li, Jie; Jiao, Xinan; Huang, Jinlin (Frontiers in Microbiology, 2021)
Although campylobacteriosis is a zoonotic foodborne illness, high-risk isolates from animal sources are rarely characterized, and the pathogenic potential of zoonotic strains remains an obstacle to effective intervention against human infection. HS19 has been knowledged as a maker serotype represent by Campylobacter jejuni (C. jejuni) isolates from patients with post-infection Guillain-Barré syndrome (GBS), which is circulating in developed countries. However, a previous serotype epidemiological study of C. jejuni isolates in an animal population revealed that HS19 was also prevalent in isolates from cattle in China. In this study, to investigate the hazardous potential of zoonotic strains, 14 HS19 isolates from cattle were systematically characterized both by genetype and phenotype. The results showed that all of these cattle isolates belonged to the ST-22 complex, a high-risk lineage represented by 77.2% HS19 clinical isolates from patients worldwide in the PubMLST database, indicating that the ST-22 complex is the prominent clonal complex of HS19 isolates, as well as the possibility of clonal spread of HS19 isolates across different regions and hosts. Nevertheless, these cattle strains clustered closely with the HS19 isolates from patients, suggesting a remarkable phylogenetic relatedness and genomic similarity. Importantly, both of tetracycline genes tet(O) and gyrA (T86I) reached a higher proportional representation among the cattle isolates than among the human clinical isolates. A worrying level of multidrug resistance (MDR) was observed in all the cattle isolates, and two MDR profiles of the cattle isolates were also existed in human clinical isolates. Notably, although shared with the same serotype HS19 and sequence type ST-22, 35.7% of cattle isolates induced severe gastrointestinal pathology in IL-10−/− C57BL/6 mice model, indicating that some bacteria could change due to host adaptation to induce a disease epidemic, thus the associated genetic elements deserve further investigation. In this study, HS19 isolates from cattle were first characterized by a systematic evaluation of bacterial genomics and in vitro virulence, which improved our understanding of the potential zoonotic hazard from food animal isolates with high-risk serotypes, and provided critical information for the development of targeted C. jejuni mitigation strategies.